2013
DOI: 10.1371/journal.pone.0054111
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of miRNA Signature Differentially Expressed in Doxorubicin-Resistant and Parental Human Hepatocellular Carcinoma Cell Lines

Abstract: Chemotherapy regiments have been widely used in the treatment of a variety of human malignancies including hepatocellular carcinoma (HCC). A major cause of failure in chemotherapy is drug resistance of cancer cells. Resistance to doxorubicin (DOX) is a common and representative obstacle to treat cancer effectively. Individual microRNA (miRNA) has been introduced in the evolution of DOX resistance in HCC in recent studies. However, a global and systematic assessment of the miRNA expression profiles contributing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…RNA samples was then examined for sample quality and subjected to deep sequencing. Small RNA library construction and sequencing were conducted as previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA samples was then examined for sample quality and subjected to deep sequencing. Small RNA library construction and sequencing were conducted as previously described …”
Section: Methodsmentioning
confidence: 99%
“…For quantitative real‐time PCR (qRT‐PCR) experiments, 500 μL of plasma was thawed on ice and used for RNA isolation with TRIZOL (Invitrogen) in accordance with the manufacture's protocol. cDNAs were prepared by Revert Aid First Strand cDNA Synthesis Kit (Thermo Scientific, Waltham, MA, USA) . For RNA extraction of blood cells, PBMCs were separated from 500 μL peripheral blood by Ficoll‐Hypaque density gradient centrifugation, of which the RNA was isolated with TRIZOL (Invitrogen) in accordance with the manufacture's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Although non-coding RNAs have diverse functions, much recent focus has been on miRNAs, particularly examining their ability to modulate known mechanisms of resistance through suppression of mRNA translation. By comparing miRNA expression patterns in doxorubicin-sensitive and doxorubicin-resistant tumors a number of resistance-associated miRNA changes have been observed [104,105]. Some of these have been shown to cause resistance while others have a plausible mechanism for inducing resistance that has not yet been proven.…”
Section: Molecular Mechanisms Of Doxorubicin Resistancementioning
confidence: 99%
“…The clean reads were then blasted against GeneBank and Rfam database for classification and annotation of non‐coding RNAs other than miRNAs (Figure ). Both of the total rRNA proportion in the two libraries were less than 40%, which showed that the animal samples were of high quality (Zhang et al, ). In terms of reads number, rRNA was the most common one, followed in descending order by snoRNA, tRNA, and snRNA.…”
Section: Resultsmentioning
confidence: 99%